2001
DOI: 10.2308/jmar.2001.13.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Communicating and Controlling Strategy: An Empirical Study of the Effectiveness of the Balanced Scorecard

Abstract: This paper reports evidence on the effectiveness of the Balanced Scorecard (BSC) as a strategy communication and management-control device. This study first reviews communication and management control literatures that identify attributes of effective communication and control of strategy. Second, the study offers a model of communication and control applicable to the BSC. The study then analyzes empirical interview and archival data to model the use and assess the communication and control effectiveness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 536 publications
(109 citation statements)
references
References 33 publications
1
69
0
6
Order By: Relevance
“…Manufacturing plants that link their strategies to their performance measurement systems through the use of the BSC were able to improve their organizational performance (Sim and Koh, 2001). The BSC may also be a management control mechanism and a means for the improvement of organizational outcomes (Malina and Selto, 2001). However, this argument suggested that the very act of performance measurement reveals deficiencies, but it did not consider the cause and effect relationships among the perspectives.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Manufacturing plants that link their strategies to their performance measurement systems through the use of the BSC were able to improve their organizational performance (Sim and Koh, 2001). The BSC may also be a management control mechanism and a means for the improvement of organizational outcomes (Malina and Selto, 2001). However, this argument suggested that the very act of performance measurement reveals deficiencies, but it did not consider the cause and effect relationships among the perspectives.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The proposition that BSC measures are generalizable among all organizations or even within an industry is notably absent in the literature. Rather, the research posits that the measures are unique to an organization or even the sub-unit of an organization (Malina and Selto, 2001). Once the criteria within the four perspectives are determined, the data and data analysis methods by which performance will be measured must be clarified (Sink and Smith, 1999).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…A grande vantagem do BSC passa a ser uma clara explicitação da estratégia empresarial (o que queremos, como e porquê), que facilita a sua compreensão numa dimensão mais operacional ou tácita (MALINA; SELTO, 2001). Aqui estão implícitas outras características das organizações de aprendizagem: clarificação da sua missão e objetivos, feedback.…”
Section: O Bsc Como Meio Para Explicitar a Estratégiaunclassified